KNOWLEDGE INVENTORY OF ETHNOCYMIA BASED ON ACEH LOCAL WISDOM FOR CHEMICAL LECTURE DEVELOPMENT - Seprianto, Seprianto; Jofrishal, Jofrishal (Jurnal Pengajaran MIPA, 2019)
Ethnochemistry is a chemical applied by certain cultural groups. This study aims to obtain information and descriptions of what ethnochemistry practiced by the Acehnese tribe in East Aceh and what potential of ethnochemistry can be developed in chemistry lectures. This research was carried out in East Aceh Regency and Langsa City. The research subjects consisted of teachers, lecturers, administrators of the Majelis Adat Aceh (MAA) and community leaders from East Aceh who were well acquainted with ethnochemical practices in the community. This research is a qualitative research model with ethnographic methods. The stages of the study included the theoretical study stage, namely literacy studies on ethnography of Acehnese tribal communities and applied chemistry and the stages of empirical study or data collection to inventory the ethnochemical knowledge practiced by the Acehnese people. Data collection was carried out using observation techniques, documentary studies, and interviews with research instruments include observation sheets, documentation, and interview guidelines. Data analysis techniques in research use a qualitative approach. Data obtained from interviews, observations, and documentation are analyzed simultaneously by first sorting out similar data (categorization) and then doing data reduction, presentation, and conclusions as well as verification. The results of the study showed that the ethnochemical knowledge of the tribes of Aceh in East Aceh that could be developed in chemistry lectures included the analysis of chemical studies on: natural ingredients used as medicines; natural ingredients used as food additives; natural ingredients used as beauty and cleaning tools and materials; appropriate technology; and processing typical Acehnese food.  ABSTRAKEtnokimia adalah kimia yang diterapkan oleh kelompok budaya tertentu. Penelitian ini bertujuan untuk memperoleh informasi dan deskripsi tentang etnokimia apa saja yang dipraktikkan suku Aceh di Aceh Timur dan potensi apa saja dari etnokimia tersebut yang dapat dikembangkan dalam perkuliahan kimia. Penelitian ini dilaksanakan di Kabupaten Aceh Timur dan Kota Langsa. Subjek penelitian terdiri dari guru, dosen, pengurus Majelis Adat Aceh (MAA) serta tokoh masyarakat asal Aceh Timur yang mengenal betul praktik etnokimia di masyarakat. Penelitian ini merupakan model penelitian kualitatif dengan metode etnografi. Tahapan penelitian meliputi tahap kajian teori yaitu studi literasi tentang etnografi masyarakat suku Aceh dan terapan ilmu kimia serta tahap kajian empirik atau pengumpulan data untuk menginventarisasi pengetahuan etnokimia yang dipraktikkan masyarakat Aceh. Pengumpulan data dilakukan dengan menggunakan teknik pengamatan, studi dokumenter, dan wawancara dengan instrumen penelitian meliputi lembar observasi, dokumentasi dan pedoman wawancara. Teknik analisis data dalam penelitian menggunakan pendekatan kualitatif. Data yang diperoleh dari wawancara, pengamatan, dan dokumentasi dilakukan analisis secara simultan dengan terlebih dahulu melakukan pemilahan data yang sejenis (kategorisasi) selanjutnya dilakukan reduksi data, penyajian, dan kesimpulan serta verifikasi. Hasil penelitian menunjukkan pengetahuan etnokimia suku Aceh di Aceh Timur yang dapat dikembangkan dalam perkuliahan kimia meliputi analisis kajian kimia tentang: bahan alam yang dijadikan obat-obatan; bahan alam yang dijadikan zat aditif makanan; bahan alam yang dijadikan alat dan bahan kecantikan serta pembersih; teknologi tepat guna; dan pengolahan makanan khas Aceh. Keywords: Aceh, ethnochemistry, inventory, local wisdom, etnokimia, inventarisasi, kearifan lokal.